Students’ Perceptions On The Use Of Kahoot! Learning Platform In Supporting Memory Retention In English Language Learning: A Descriptive Qualitative Study - Maifa, Leni; Elmiana, Dewi Satria; Putera, Lalu Jaswadi (LITPAM, 2026)
Rendahnya hasil belajar PKn siswa kelas IV SD Muhammadiyah Desa Pon serta pembelajaran yang masih The use of digital game-based learning platforms has grown significantly in English language teaching; however, many students still struggle with retaining vocabulary and grammar over time due to limited opportunities for meaningful repetition and engaging practice. This study aims to explore students' perceptions on the use of the Kahoot! learning platform in supporting memory retention in English language learning. This research employed a descriptive qualitative design and was conducted at MAN 3 Mataram. The participants of this study were 15 students selected purposively. The data were collected through questionnaires and semi-structured interviews to obtain in-depth information about students' experiences. The findings indicate that students generally have positive perceptions toward the use of Kahoot! in the classroom. Specifically, 71% of responses related to learning experience were positive, indicating that Kahoot! creates an interactive and enjoyable learning environment that encourages students' active participation. In terms of memory retention, 67% of responses were positive. Students reported that Kahoot! supports their memory retention through three main factors: repetition (repeated exposure to similar questions strengthens memory), retrieval practice (recalling information within time limits encourages active thinking), and contextual learning (visual elements such as images help connect words with their meanings). However, some difficulties were also found, such as time limitations and internet connectivity issues. The practical implications of these findings for English teachers are that Kahoot! can be strategically integrated as a complementary tool for vocabulary and grammar review, used at the beginning or end of lessons to activate prior knowledge and reinforce learning through low-stakes repetition. Teachers should balance game-based activities with direct instruction and classroom discussion to ensure deeper understanding, and they need to anticipate technical constraints by preparing offline backup activities or ensuring stable internet access. Overall, Kahoot! is perceived as a useful tool in supporting students' memory retention in English language learning.